KINERJA UNIT PELAYANAN PENDAPATAN DAN PEMBERDAYAAN ASET DAERAH KOTA SALATIGA DIUKUR DENGAN BALANCED SCORECARD - Untung Sriwidodo, Wahyuningrum Anggraeni, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The purpose of this study are to: 1) to analyze performance UP3ADSalatiga city with Balanced Scorecard ie by financial perspective 2) toanalyze performance UP3AD Salatiga city with Balanced Scorecard ie byconsumer perspective 3) to analyze performance UP3AD Salatiga city withBalanced Scorecard ie by internal business perspective 4) to analyzeperformance UP3AD Salatiga city with Balanced Scorecard ie by learn andgrowth The population of the UP3AD Salatiga City some 60 people, sampleswere collected by the census of the number of existing data collectiontechniques through questionnaires or questionnaiare with validity andreliability analysts techniques using multiple linear regression with theclassical assumption. The results obtained by analysis of all the variablesthat is financial perspective, consumer perspective, internal businessperspective and learn and growth perspective take effect on performanceUP3AD Salatiga City.Keywords: financial, consumer, internal businnes, learn and growth,performance UP3AD